2018
DOI: 10.1186/s12887-018-1277-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, dental caries and tooth eruption in children: a longitudinal study in Cambodia, Indonesia and Lao PDR

Abstract: BackgroundUntreated dental caries is reported to affect children’s nutritional status and growth, yet evidence on this relationship is conflicting. The aim of this study was to assess the association between dental caries in both the primary and permanent dentition and nutritional status (including underweight, normal weight, overweight and stunting) in children from Cambodia, Indonesia and Lao PDR over a period of 2 years. A second objective was to assess whether nutritional status affects the eruption of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 37 publications
5
76
0
11
Order By: Relevance
“…It has been known throughout history but started to become a significant health problem in industrialized countries in the latter part of the nineteenth century, when new technologies allowed the production of large amounts of refined sugars. Globally prevalence indicates about 60-90% of children and nearly 100% of the adult world population is suffering from dental caries [2,3]. While WHO reports that untreated caries accounts for 44% dental problems in 2010 [4], lack of oral hygiene practices is common problem in many developing and developed countries [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known throughout history but started to become a significant health problem in industrialized countries in the latter part of the nineteenth century, when new technologies allowed the production of large amounts of refined sugars. Globally prevalence indicates about 60-90% of children and nearly 100% of the adult world population is suffering from dental caries [2,3]. While WHO reports that untreated caries accounts for 44% dental problems in 2010 [4], lack of oral hygiene practices is common problem in many developing and developed countries [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…in the major progression of dental caries [8]. In addition, risk factors such as host susceptibility [9], age [10], dietary habits [11], socioeconomic and oral hygiene status [12] have been associated with increased incidence of dental caries [3,13,14] in human population.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence and advanced prevention techniques of dental caries have contributed to the reduction in the prevalence of dental caries [ 1 , 2 , 3 , 4 , 5 ]; however, in developing countries, the prevalence of dental caries in children remains high and is one of the major public health concerns [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In these countries, dental treatment is still insufficient [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the WHO recommends that nutritional assessment and support should be an integral part of the care plan for children living with HIV [11]. Such support needs to include interventions to improve oral health as untreated dental caries and a delayed eruption of permanent teeth are associated with underweight and stunting among children in Cambodia, Indonesia and Lao PDR [34]. The timing of such nutritional interventions is also important: a recent study suggested that the first year on ART could be the best period to conduct nutritional interventions for children living with HIV to optimize their growth in the long term [35].…”
Section: Discussionmentioning
confidence: 99%